The Holy Spirit and Christian mission : in a pluralistic context - George, Roji T (ed.) (Bengaluru, SAIACS., 2017)
This is a collection of articles from various church backgrounds and theological viewpoints. It reaffirms the necessity and urgency of a pneumatic missiology. It does not speak of God's saving mission as originating simply from God; it highlights the central role of the Spirit in the effective mission of the church. -- From publisher's description
Keywords: Missions; Holy Spirit; Missions.-- India; Missions.-- Theory; Pentecostalism; Religious pluralism.-- Christianity